1997
DOI: 10.1038/43191
|View full text |Cite
|
Sign up to set email alerts
|

Fringe modulates Notch–ligand interactions

Abstract: The Notch family of transmembrane receptor proteins mediate developmental cell-fate decisions, and mutations in mammalian Notch genes have been implicated in leukaemia, breast cancer, stroke and dementia. During wing development in Drosophila, the Notch receptor is activated along the border between dorsal and ventral cells, leading to the specification of specialized cells that express Wingless (Wg) and organize wing growth and patterning. Three genes, fringe (fng), Serrate (Ser) and Delta (Dl), are involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
443
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(460 citation statements)
references
References 32 publications
(39 reference statements)
14
443
1
2
Order By: Relevance
“…Because lunatic fringe has been proposed to potentiate Notch-Delta signaling (Panin et al, 1997;Moloney et al, 2000), we tested whether lunatic fringe over-expression altered the levels or distribution patterns of members of the Notch signaling pathway to better understand the mechanisms by which lunatic fringe might regulate trunk neural crest production. In particular, we examined the effects of excess lunatic fringe on Notch-1 and its ligand Delta-1.…”
Section: Effects Of Lunatic Fringe Over-expression On Notch-1 and Delmentioning
confidence: 99%
“…Because lunatic fringe has been proposed to potentiate Notch-Delta signaling (Panin et al, 1997;Moloney et al, 2000), we tested whether lunatic fringe over-expression altered the levels or distribution patterns of members of the Notch signaling pathway to better understand the mechanisms by which lunatic fringe might regulate trunk neural crest production. In particular, we examined the effects of excess lunatic fringe on Notch-1 and its ligand Delta-1.…”
Section: Effects Of Lunatic Fringe Over-expression On Notch-1 and Delmentioning
confidence: 99%
“…L-fng is an ortholog of the Drosophila fringe gene that acts in the Notch signaling pathway to establish boundaries during the development of both flies and vertebrates (Laufer et al 1997;Panin et al 1997;Evrard et al 1998;Papayannopoulos et al 1998;Zhang and Gridley 1998). Recent data show that Fringe mediates its effect by forming complexes with Notch receptors and modulating their ligand preferences (Hicks et al 2000;Ju et al 2000).…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…Genetic studies in Drosophila have indicated the existence of Notch modifying genes such as numb and fringe. 34,35 For example, association of Fringe with Notch-1 impairs Serrate (Jagged)-mediated signaling, but is permissive for Delta-mediated signaling. 36 Mammalian homologues of these genes have been identified.…”
Section: Figurementioning
confidence: 99%